Conservation of Malkangiri ponies, a native breed in Southern Odisha - Kalyanapu, Uday Kumar; Dash, Susant Kumar; Mohanty, Abhijit; Das, Sabyasachi (Journal of Livestock Biodiversity, 2025)
The Malkangiri pony, a unique indigenous horse breed found in Southern Odisha, India, plays a crucial role in preserving biodiversity and supporting local livelihoods. The present study was aimed to evaluate the pony in its native tract. The average height at withers of these ponies was recorded as 125.86±0.34 and 123.77±0.38 cm in male and female, respectively. Height at croup was found to be around 3 cm less than the height at withers. Body length was 106.85±0.19 cm in stallion and corresponding value for mares was 105.26±0.23 cm. An adult pony of either sex is capable of carrying up to 120 kg of weight in undulated hilly terrain. Age at first foaling was estimated as 45.53±1.25 months. The mean foaling interval of these ponies was found as 19.45±0.64 months with gestation period of 11 months. Preserving the Malkangiri pony not only contributes to the genetic diversity of livestock but also supports local agriculture, transportation and tourism, triggering enhancement of livelihood of the stakeholders.